Therapeutic Drug Monitoring of Sputum Voriconazole in Pulmonary Aspergillosis - Sacha Sarfati; Julien Wils; Timothée Lambert; Céline Mory; Laurent Imbert; Gilles Gargala; Hélène Morisse-Pradier; Fabien Lamoureux (MDPI AG, 2022)
Voriconazole is one of the most used antifungal azoles against pulmonary aspergillosis. Therapeutic drug monitoring (TDM) of the voriconazole concentration in plasma is recommended in clinical practice guidelines to prevent treatment failure and toxicity. The aim of this study was to evaluate the feasibility and utility of TDM of the voriconazole concentration in the sputum of patients treated for pulmonary aspergillosis. Fifty sputum and 31 plasma samples were analysed with high-performance tandem mass spectrometry (HPLC-MS/MS) in 24 patients included in the study. The voriconazole concentration was simultaneously assessed in the plasma and sputum in 22 samples. The correlation between the sputum and plasma levels was estimated with a univariate linear regression model, and the observed R2 was 0.86. We determined the following equation, Csputum = 0.45 (Cplasma) + 0.21, which could predict the voriconazole concentration in plasma from sputum. TDM of the voriconazole concentration in sputum is an easy, non-invasive and accurate method with which to evaluate voriconazole exposure in patients with pulmonary aspergillosis.